Antibiogram of single, double and triple chain Aroyl hydrazine against some gram positive and gram negative bacteria - Parvin, R; Absar, MN; Ershaduzzaman, M; Mahbub-E-Elahi, ATM; Shil, A (International Journal of Natural Sciences, 2011)
The antibacterial sensitivity of some single, double and triple chain aroylhydrazine against gram positive and gram negative bacteria were performed by disc diffusion method. Most of the compounds showed appreciable antibacterial activity against different gram positive and gram negative bacteria. The single chain hydrazines are more active then double chain and triple chain hydrazine. Among the single chain aroylhydrazines studied only 4-n-hexyloxy benzoyl hydrazine is the most active. The significant activity of 4-n-hexyloxybenzoyl hydrazine and heptyloxybenzoyl hydrazine against gram positive and gram negative bacteria may be (formation of inhibition zone 8 to 22 mm with most of the test bacteria) due to their liophilicity of the bacterial cell membrane. Anti-microbial activity decreases as the number of carbon of single chain hydrazine increases (C6 > C7 > C8 > C9 > C10 single chain hydrazine). Double chain hydrazines (3, 5 or 3, 4) are more active than triple chain hydrazines (3, 5 > 3, 4 > 3, 4, 5 hydrazine). The antibacterial activities of hydrazines are being decreased as their increasing number of side chain. Keyword: Antibacterial sensitivity; Aroyl hydrazine. DOI: http://dx.doi.org/10.3329/ijns.v1i1.8610 International Journal of Natural Sciences (2011), 1(1):17-21